Benefits of Qigong as an integrative and complementary practice for health: a systematic review - Bruna Francielle Toneti; Rafael Fernando Mendes Barbosa; Leandro Yukio Mano; Luana Okino Sawada; Igor Goulart de Oliveira; Namie Okino Sawada (Universidade de São Paulo, 2020)
Objective: to analyze, in the literature, evidence about the benefits of the integrative and complementary practice of Qigong with regard to the health of adults and the elderly. Method: a systematic review by searching for studies in the PubMed, CINAHL, LILACS, EMBASE and Cochrane Library databases. Randomized and non-randomized clinical trials were included; in Portuguese, English and Spanish; from 2008 to 2018. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses strategy was adopted, as well as the recommendation of the Cochrane Collaboration for assessing the risk of bias in the clinical trials analyzed. Results: 28 studies were selected that indicated the benefit of the practice to the target audience, which can be used for numerous health conditions, such as: cancer; fibromyalgia; Parkinson's disease; Chronic Obstructive Pulmonary Disease; Burnout; stress; social isolation; chronic low back pain; cervical pain; buzz; osteoarthritis; fatigue; depression; and cardiovascular diseases. However, there was a great risk of bias in terms of the blinding of the research studies. Conclusion: the practice of Qigong produces positive results on health, mainly in the medium and long term. This study contributes to the advancement in the use of integrative and complementary practices in nursing, since it brings together the scientific production in the area from the best research results available.